The Role of The Community and Village Empowerment Service, Organizational Commitment and Community Supervision of The Accountability of Village Fund Allocation Management in Berau Regency with The Implementation of SISKEUDES as an Intervening Variable (Literature Study) - Suryadinata, Dede; Jauhar Tantowi, Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The management of Village Fund Allocation (ADK) in Berau Regency is a crucial concern as it relates to effective, transparent, and sustainable village development. The Village and Community Empowerment Agency (DPMK) acts as a facilitator and supervisor, while the organizational commitment of village officials and community oversight are determining factors in the accountability of ADK management. This research is important to examine the relationship between the role of DPMK, organizational commitment, and community oversight with the accountability of ADK management through the comprehensive implementation of SISKEUDES. The purpose of this study is to analyze in depth how the role of the Village Fund Management Agency (DPMK), organizational commitment, and community oversight influence the accountability of ADK management in Berau Regency, with the implementation of SISKEUDES as an intervening variable. This study employed a qualitative method with a literature review approach. Various sources, such as national journals, government reports, and previous research findings, were analyzed thematically. The literature review shows that the active role of the Village Fund Management Agency (DPMK) in training and mentoring improves village officials' understanding of the use of SISKEUDES. Strong organizational commitment encourages transparency in financial reporting, while community oversight has been shown to improve procedural compliance. This study concludes that the synergy of the roles of the Village Fund Management Agency (DPMK), organizational commitment, and community oversight significantly influences the accountability of ADK management in Berau Regency.